2003
DOI: 10.1080/714040495
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model for Motorcycle Accidents at Three-Legged Priority Junctions

Abstract: SlrltslrcS |.evcirl thal .jLructioDs are liccidenl-pl'orrc iu eas Lree;Luse lr lllge ;lroporlion of accidenls hrrve lreeri rcpr)rtcd ro or'cur at junctions (l lE, 2002; PDR\,1. 2002). f)cspitc. rrnprovcd .luncLion desisn ;rncl nxrrc sollhtsticated applioalion of trliTic err-pttrtccrin{ ir)oirsu|es. Lhc rnnLrtrl dcrth toll du!: to tftf{ic lcciclenls lres not cl)ange(l subslantillly in rlorc lhau 25 years (IT8.2002). llascd on thc ltiescnL aciitlerrt scsllario, thet'e is an urgcnt neecl lo sPr'cinllJ, (L.stqrr t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…This is in line with the findings of previous studies on gapacceptance and time-to-arrival, which pointed out that the most common cause of motorcycle-automobile gap acceptance accidents was motorists infringing motorcyclists' right of way (Harnen et al, 2003;Pai, 2011;Pai et al, 2009;Radin Umar, 2005;Thomson, 1980). Still, our observations also showed that the majority of these serious conflicts occurred more frequently between motorcyclists who entered the primary road and passenger cars on the primary road.…”
Section: Manner Of Entering the Flow Of The Primary Roadsupporting
confidence: 94%
“…This is in line with the findings of previous studies on gapacceptance and time-to-arrival, which pointed out that the most common cause of motorcycle-automobile gap acceptance accidents was motorists infringing motorcyclists' right of way (Harnen et al, 2003;Pai, 2011;Pai et al, 2009;Radin Umar, 2005;Thomson, 1980). Still, our observations also showed that the majority of these serious conflicts occurred more frequently between motorcyclists who entered the primary road and passenger cars on the primary road.…”
Section: Manner Of Entering the Flow Of The Primary Roadsupporting
confidence: 94%
“…By comparison, a somewhat smaller proportion of all vehicle crashes (25%) occur at T-junctions and 17% at crossroads; this statistic suggests that this finding is unlikely to be due to greater exposure to T-junctions than to other intersection types (5). Similar findings in Malaysia have led to the development of specific engineering treatments to reduce such risks for PTWs (22,23).…”
Section: Discussion Of Resultsmentioning
confidence: 60%
“…The final model was based on the goodness of fit and the significance test carried out on the models, such as the change in scaled deviance from adding or removing the terms, the ratio of scaled deviance to its degree of freedom (mean deviance) and 't' values of the parameter estimates are significant at 5% significance level. Based on the multivariate analysis, the final model (Harnen et al 2003) where MCA is motorcycle accidents per year, b 5 ¼ 0.0, 0.00903 and 0.02099 for SHDW ¼ 1, 2 and 3, respectively, b 6 ¼ 0.0 and 0.00755 for LU ¼ 1 and 2, respectively. Malaysia 75 The model suggests that the number of motorcycle accidents is proportional to the power of traffic flow.…”
Section: Junction Accident Models and Treatment Criteriamentioning
confidence: 99%